Cyclic Peptides for Efficient Detection of Collagen. (21st June 2018) - Takita, Koh K.; Fujii, Kazunori K.; Kadonosono, Tetsuya; Masuda, Ryo; Koide, Takaki
Abstract: We report here a new class of collagen‐binding peptides, cyclic collagen‐mimetic peptides (cCMPs), that efficiently hybridize with the triple‐helix‐forming portions of collagen. cCMPs are composed of two parallel collagen‐like (Xaa‐Yaa‐Gly) n strands with both termini tethered by covalent linkages. Enzyme‐linked immunosorbent assays and western blotting analysis showed that cCMPs exhibit more potent affinity toward collagen than reported collagen‐binding peptides and can specifically detect different collagen polypeptides in a mixture of proteins. Collagen secreted from cultured cells was detected by confocal microscopy with fluorescein‐labeled cCMP. The cCMP is also shown to detect sensitively folding intermediates in the endoplasmic reticulum, something that was difficult to visualize with conventional collagen detectors. Molecular‐dynamics simulations suggested that a cCMP forms a more stably hybridized product than its single‐chain counterpart; this could explain why cCMP has higher affinity toward denatured collagen. These results indicate the usefulness of cCMPs as tools for detecting denatured collagen. Abstract : Detection of collagen : The cyclic collagen‐mimetic peptide (cCMP) hybridizes efficiently with denatured portions of the collagen triple helix. Such cCMP compounds can be used to detect various types of collagen polypeptide by western blotting or, with fluorescein‐labeled cCMP, to visualize damaged collagen fibrils secreted from cultured cells and folding intermediates in the endoplasmic reticulum.